Autophagy is essential for maintaining the growth of a human (mini-)organ: Evidence from scalp hair follicle organ culture - Parodi, Chiara; Hardman, Jonathan A.; Allavena, Giulia; Marotta, Roberto; Catelani, Tiziano; Bertolini, Marta; Paus, Ralf; Grimaldi, Benedetto (PLOS Biology, 2018)
Author summary Human scalp hair follicles (HFs) experience a massive growth for years, until they spontaneously enter into a rapid, apoptosis-driven organ involution process, orchestrated by an organ-intrinsic “hair cycle clock,” the molecular control of which remains unclear. Human HFs maintain in vivo–like characteristics, even after being removed from the body, and spontaneously run through a fundamental organ-remodelling process, traversing through a stage of growth (anagen) and destruction (catagen) as a (mini-)organ model. Here, we exploit this unique remodelling (mini-)organ to unveil a crucial new role of autophagy in the growth of human HFs. We show that hair matrix keratinocytes exhibit an active autophagic flux ex vivo during anagen, which is altered after the transition to catagen. We find that genetic inhibition of follicular autophagy induces premature catagen and enhances hair matrix keratinocyte apoptosis, suggesting that autophagic flux in the anagen hair matrix is important for the maintenance of this stage. Indeed, we find that the principal ingredients of a product used to treat hair loss induces autophagy in organ-cultured human scalp HFs and promotes anagen. We conclude that organ-cultured human HFs are a suitable (mini-)organ system to study both the role of autophagy in human physiology ex vivo and to test candidate agents that modulate autophagy under clinically relevant conditions.